Case report: Thirty-year progression of an EMPF1 encephalopathy due to defective mitochondrial and peroxisomal fission caused by a novel de novo heterozygous DNM1L variant - Lhuissier, Charlène; Wagner, Bart E.; Vincent, Amy; Garraux, Gaëtan; Hougrand, Olivier; Van Coster, Rudy; Benoit, Valerie; Karadurmus, Deniz; Lenaers, Guy; Gueguen, Naïg; Chevrollier, Arnaud; Maystadt, Isabelle (Frontiers in Neurology, 2022)
Mutations in DNM1L (DRP1), which encode a key player of mitochondrial and peroxisomal fission, have been reported in patients with the variable phenotypic spectrum, ranging from non-syndromic optic atrophy to lethal infantile encephalopathy. Here, we report a case of an adult female patient presenting with a complex neurological phenotype that associates axonal sensory neuropathy, spasticity, optic atrophy, dysarthria, dysphasia, dystonia, and ataxia, worsening with aging. Whole-exome sequencing revealed a heterozygous de novo variant in the GTPase domain of DNM1L [NM_001278464.1: c.176C>A p.(Thr59Asn)] making her the oldest patient suffering from encephalopathy due to defective mitochondrial and peroxisomal fission-1. In silico analysis suggested a protein destabilization effect of the variant Thr59Asn. Unexpectedly, Western blotting disclosed profound decrease of DNM1L expression, probably related to the degradation of DNM1L complexes. A detailed description of mitochondrial and peroxisomal anomalies in transmission electron and 3D fluorescence microscopy studies confirmed the exceptional phenotype of this patient.